Repair and renovation of concrete structures proceedings of the international conference held at the University of Dundee, Scotland, UK on 5-7 July 2005 - Dhir, Ravindra K.; Jones, M. Roderick; Zheng, Li, 1958- (Thomas Telford, 2005)
Concrete faces many opportunities and some threats. For these opportunities to change into beneficial practice, engineers, material scientists, architects, manufactureres and suppliers must focus on the changes needed to champion concrete and maintain its dominance within the global construction industry.